1998
DOI: 10.1002/(sici)1097-0215(19980504)76:3<317::aid-ijc5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations in sweat gland carcinomas

Abstract: Sweat gland carcinomas are rare skin tumours and little is known about their etiology and molecular basis. In this study, we analyzed p53 mutations in 16 sweat gland carcinomas with different histologic types, including 2 spiradenocarcinomas, 1 composed adnexal carcinoma, 5 porocarcinomas, 2 eccrine hidradenocarcinomas, 2 syringocystadenocarcinomas, 1 sclerosing sweat gland carcinoma, 1 adenoid cystic carcinoma, 1 cylindrocarcinoma and 1 apocrine adenocarcinoma. Single‐stranded conformation polymorphism (SSCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Two of eleven hidradenocarcinomas exhibited TP53 mutations in the series by Kazakoz et al . [17] Similar to findings reported by Biernat et al [15] and Kazakov et al [17], we found TP53 mutations in codon 248 of exon 7 and codon 273 of exon 8 in our 7 positive cases ( Table 5 ). Interestingly, these same mutations have also been reported in breast carcinomas [40][42].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Two of eleven hidradenocarcinomas exhibited TP53 mutations in the series by Kazakoz et al . [17] Similar to findings reported by Biernat et al [15] and Kazakov et al [17], we found TP53 mutations in codon 248 of exon 7 and codon 273 of exon 8 in our 7 positive cases ( Table 5 ). Interestingly, these same mutations have also been reported in breast carcinomas [40][42].…”
Section: Discussionsupporting
confidence: 91%
“…TP53 mutations are usually clustered within the most conserved regions of exons 4, 5, 7, and 8 [39]. TP53 mutations have been previously described in apocrine-eccrine carcinomas ( Table 5 ) [15][19]. Takata et al [18] performed PCR based assays for loss of heterozygosity on chromosomes 3p, 5q, 9p, 9q, 13q, and 17p; yet found only 1 case with TP53 mutation by direct sequencing of exons 5 to 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Mutation of the p53 gene and increased levels of p53 protein are among the most frequent alterations in malignant sweat gland tumors. 18,19 Sweat gland carcinomas showing c-erbB-2 expression had a high p53 index, and a higher p53 index was associated with a poor prognosis. 20 Our case showed positive staining for cytokeratin and c-erbB-2.…”
Section: Discussionmentioning
confidence: 99%